The Ashgate research companion to federalism [ - Ward, Ann , 1970-; Ward, Lee (Ashgate research companion, 2009)
This comprehensive research companion examines the theory, practice and historical development of the principle of federalism from the ancient period to the contemporary world. The scope and range of the volume is unparalleled; it will provide the reader with a firm understanding of federalism as issues of federalism promise to play an ever more important role in shaping our world